2021
DOI: 10.1021/acsami.1c16988
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Predictions of Out-of-Plane Group IV and V Dimers as High-Symmetry, High-Spin Defects in Hexagonal Boron Nitride

Abstract: Hexagonal boron nitride (h-BN) has been recently found to host a variety of quantum point defects, which are promising candidates as single-photon sources for solid-state quantum nanophotonic applications. Most recently, optically addressable spin qubits in h-BN have been the focus of intensive research due to their unique potential in quantum computation, communication, and sensing. However, the number of highsymmetry, high-spin defects that are desirable for developing spin qubits in h-BN is highly limited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…In addition to the above mentioned works, there are many efforts to find high-spin defects which are key quantities to develop nanoscale sensors [167,168]. Bhang et al [167] reported that out-of-plane X N Y i dimer defects (X, Y = C, N, P, and Si) form a new class of stable C 3v spin-triplet (S = 1) defects in hBN. Smart et al [168] reported that Ti VV and Mo VV defects in hBN have a neutral triplet GS (S = 1).…”
Section: Other Defectsmentioning
confidence: 99%
“…In addition to the above mentioned works, there are many efforts to find high-spin defects which are key quantities to develop nanoscale sensors [167,168]. Bhang et al [167] reported that out-of-plane X N Y i dimer defects (X, Y = C, N, P, and Si) form a new class of stable C 3v spin-triplet (S = 1) defects in hBN. Smart et al [168] reported that Ti VV and Mo VV defects in hBN have a neutral triplet GS (S = 1).…”
Section: Other Defectsmentioning
confidence: 99%
“…Recently, simulations for out‐of‐plane defects, in particular group IV and V dimers, have been performed and discussed in the context of high‐symmetry, high‐spin defect centers. [ 116 ] Applying similar modeling to the orbital structure of mechanically isolated defect centers could be a promising path forward to investigate the underlying decoupling mechanism. The apparent universality of the mechanical isolation mechanism, resulting in isolated emitters with a large range of ZPL transition wavelengths, enables applications in a broad range.…”
Section: Future Perspectives and Applicationsmentioning
confidence: 99%
“…Furthermore, these defects were also discussed in several recent theoretical works. [21][22][23][24][25] On the other hand, no comprehensive theoretical studies have been carried out for these candidates.…”
Section: Introductionmentioning
confidence: 99%